In-service education and teachers' perception about key competences development with Sport Education - Antonio Calderón; Diego Martínez de Ojeda; Antonio Méndez (FEADEF, 2013)
The purpose of this paper was to analyze the perception of physical education teachers on job opportunities of key competences of a particular teaching model. To this end, 12 teachers, Secondary and Primary, conducted an in-service education course on the model, and once completed, implemented a teaching unit in their respective schools. It was then through a questionnaire, they were asked about their perception of the development of key competences. To check whether there were differences in the perception of teachers on the development of each of the core competencies, it was calculated means and standard deviations of all variables recorded, and used the Mann-Whitney U test for independent samples. Teachers see great potential to work competence through Sport Education Model primarily on social and civic competence, lifelong learning, and autonomy and personal initiative.